Inverse-FEM Characterization of a Brain Tissue Phantom to Simulate Compression and Indentation (2012)
The realistic simulation of tool-tissue interactions is necessary for the development of surgical simulators and one of the key element for it realism is accurate bio-mechanical tissue models. In this paper, we determined the mechanical properties of soft tissue by minimizing the diﬀerence between experimental measurements and the analytical or simulated solution of the deformation. Then, we selected the best model parameters that ﬁt the experimental data to simulate a bonded compression and a needle indentation with a ﬂat-tip. We show that the inverse FEM allows accurate material property estimation. We also validated our results using multiple tool-tissue interactions over the same specimen.